2019
DOI: 10.1111/crj.13124
|View full text |Cite
|
Sign up to set email alerts
|

Shared and unique individual risk factors and clinical biomarkers in children with allergic rhinitis and obstructive sleep apnea syndrome

Abstract: Introduction Rhinitis and obstructive sleep apnea syndrome (OSAS) are different diseases, but have some similar risk factors. Objective The aims of this study were to compare the risk factors and clinical biomarkers for rhinitis and OSAS in children. Methods We examined 3917 children (age 4‐13 years) who were enrolled in a cross‐sectional study conducted in Seongnam, Korea. Their parents completed the Pediatric Sleep Questionnaire (PSQ) for evaluation of OSAS and the International Study of Asthma and Allergies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…26 Ha and colleagues demonstrated significantly lower values of NLR in patients with AR when compared with healthy controls. 11 Similar to the results of the study conducted by Ha and colleagues, 11 we also observed significantly lower levels of NLR in AR patients versus the control group. An NLR cut-off value of ≤1.7 had 42.8% sensitivity, 73.5% specificity, and 86.5% PPV for predicting AR with an AUC of 0.602.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…26 Ha and colleagues demonstrated significantly lower values of NLR in patients with AR when compared with healthy controls. 11 Similar to the results of the study conducted by Ha and colleagues, 11 we also observed significantly lower levels of NLR in AR patients versus the control group. An NLR cut-off value of ≤1.7 had 42.8% sensitivity, 73.5% specificity, and 86.5% PPV for predicting AR with an AUC of 0.602.…”
Section: Resultssupporting
confidence: 90%
“…Growing evidence shows that absolute neutrophil, lymphocyte, and neutrophil counts and their respective ratios could be used to assess severity of AR. 11,12 In this study, 160 patients (78.0%) had persistent AR. Istanbul and Trabzon, where the research was conducted, have zero altitude and have a climate with an average relative humidity of 80-85% 13 .…”
Section: Discussionmentioning
confidence: 65%
“…Pre-term birth has previously been linked to a higher risk of OSAS ( 43 ). Breastfeeding has been shown to be positively correlated with OSAS incidence, and breastfeeding rates are higher for parents with a lower education level as compared to patients with a higher education level ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonallergic rhinitis is a diagnosis of exclusion that is characterized by signs and/or symptoms similar to allergic rhinitis (e.g., rhinorrhea, nasal obstruction, nasal itching, and sneezing after allergen exposure). After the exclusion of allergic rhinitis based on the identification of allergen sensitizations, nonallergic rhinitis is suspected and efforts are made to identify associated conditions like sinusitis or adenoid hypertrophy [ 7 , 8 ]. Studies have reported that the prevalence of nonallergic rhinitis is 0.7%–50.0 % (median, 10.1%) in pediatric population.…”
Section: Epidemiology Of Nonallergic Rhinitis In Childrenmentioning
confidence: 99%
“…After the exclusion of allergic rhinitis based on the identification of allergen sensitizations, nonallergic rhinitis is suspected and efforts are made to identify associated conditions like sinusitis or adenoid hypertrophy. 7,8) Studies have reported that the prevalence of nonallergic rhinitis is 0.7%-50.0 % (median, 10.1%) in pediatric population. Nonallergic rhinitis seems to account for 15.7%-89.0% of the chronic rhinitis cases (Table 1).…”
Section: Epidemiology Of Nonallergic Rhinitis In Childrenmentioning
confidence: 99%